The sticking coefficient of H2 on Ni(111) as a function of particle energy and angle of incidence: A test of detailed balancing - Steinrück, Hans-Peter; Rendulic, K.D.; Winkler, A. (Surface Science, 1985)
The sticking coefficient of H/Ni(111) changes proportionally to the beam energy. The angular distribution of the probability of adsorption varies with cosθ; the angular distribution of desorption is found to change as cosθ at 300 K. Assuming validity of detailed balancing, the adsorption data suggest an energy distribution for desorption which agrees with existing time-of-flight measurements. © 1985.